2020
DOI: 10.1093/molbev/msaa249
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Gene Decay in Subterranean Vertebrates: Insights from Cavefishes and Fossorial Mammals

Abstract: Evolution sometimes proceeds by loss, especially when structures and genes become dispensable after an environmental shift relaxes functional constraints. Subterranean vertebrates are outstanding models to analyze this process, and gene decay can serve as a readout. We sought to understand some general principles on the extent and tempo of the decay of genes involved in vision, circadian clock and pigmentation in cavefishes. The analysis of the genomes of two Cuban species belonging to the genus Lucifuga provi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 54 publications
(48 reference statements)
9
82
0
Order By: Relevance
“…4). Interestingly, the correlation was higher when considering only the shortest terminal branches (R > 0.7 with maximum branch length < We ran simulations of sequence evolution involving nucleotide substitutions and small indels taking into account their relative frequencies estimated in a study of gene decay in teleosts (Policarpo, et al 2020). We found that about half of the pseudogenes were not detected after ~ 40 millions of generations (supplementary fig.…”
Section: Supplementary Fig S7 Supplementary Materials Online)mentioning
confidence: 99%
See 3 more Smart Citations
“…4). Interestingly, the correlation was higher when considering only the shortest terminal branches (R > 0.7 with maximum branch length < We ran simulations of sequence evolution involving nucleotide substitutions and small indels taking into account their relative frequencies estimated in a study of gene decay in teleosts (Policarpo, et al 2020). We found that about half of the pseudogenes were not detected after ~ 40 millions of generations (supplementary fig.…”
Section: Supplementary Fig S7 Supplementary Materials Online)mentioning
confidence: 99%
“…In order to estimate the time necessary for making a pseudogene undetectable through the accumulation of substitutions and small indels, we ran simulations in which an intact OR sequence accumulated nucleotide substitutions (at a rate of 10-8 per generation) and indels at a rate of 0.05 x 10 -8 per generation as estimated previously (Policarpo, et al 2020). We also took into account the transition/transversion ratio and the relative frequency of indels ranging from 1 and 9 bp in length (more details on the numerical values used for the simulations are given in the Python script available at https://github.com/MaximePolicarpo/ Olfactory_receptor_genes).…”
Section: Correlation Between the Number Of Gene Losses And The Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…While d S are assumed to evolve neutrally, d N are expected to be exposed to selection, as they change the aminoacidic structure of proteins. Despite some of these assumption have been challenged (Davydov et al, 2019; He et al, 2020), analyses based on codon models have proved themselves as key approaches in comparative genomics, such as investigating positive selection connected to evolutionary innovations (Parker et al 2013; Zhang et al 2014; Li et al 2014) or testing the relaxation of selective constraints after trait decay (Liu et al 2019; Policarpo et al 2020). In other instances, these approaches have been used to observe genome-wide effects linked to events such as shifts in environmental niches or the loss of recombination in asexual genomes (Plazzi et al, 2017; Bast et al 2018).…”
Section: Introductionmentioning
confidence: 99%